PENDAMPINGAN PENERAPAN STRATEGI PEMASARAN DALAM ERA DIGITALISASI PADA CV. AIRLANGGA TRANS - Yatnanta Ramadhana; Abdul Mu'iz Ihsan; Agus Hermawan; Agung Winarno (Rafandha Press, 2023)
As students we must implement the Tridarma of Higher Education which includes 3 points namely Education and Teaching. Research and development. Community service Community service is a topic that must be applied especially for academics to provide real comparisons both in terms of academics/textbooks and reality or real problems in the field. The purpose of this is to have a real impact on MSMEs or society so that they can develop and adapt to current conditions. In this service, we are directly involved in providing assistance and development at CV. Airlangga Trans is engaged in the car rental service industry. This company is one of the oldest car rental companies in Malang City which was founded in 1996 and was originally named Silver. CV. Airlangga Trans is located on Jl. Karimata Strait E6 No. 3-4, Lesanpuro, KedungSometimes, Malang City. The reason for this business assistance is that this business has experienced a very significant decrease in turnover because it cannot compete with other vehicle rental businesses both in terms of operations, marketing, and digitalization. The results of our real dedication and assistance are the creation of a more up-to-date logo, the creation of a clear organizational structure and job deck, a more streamlined operational flow, and the creation of digital marketing, namely Website, Instagram, TikTok, and Youtube.